The clinical and molecular diversity of mast cell leukemia with or without associated hematologic neoplasm - Jawhar, Mohamad; Schwaab, Juliana; Naumann, Nicole; Fabarius, Alice; Hofmann, Wolf-Karsten; Metzgeroth, Georgia; Reiter, Andreas (Haematologica, 2017)
Mast cell leukemia is a rare variant of advanced systemic mastocytosis characterized by at least 20% of mast cells in a bone marrow smear. We evaluated clinical and molecular characteristics of 28 patients with (n=20, 71%) or without an associated hematologic neoplasm. De novo mast cell leukemia was diagnosed in 16 of 28 (57%) patients and secondary mast cell leukemia evolving from other advanced systemic mastocytosis subtypes in 12 of 28 (43%) patients, of which 7 patients progressed while on cytoreductive treatment. Median bone marrow mast cell infiltration was 65% and median serum tryptase was 520 μg/L. C-findings were identified in 26 of 28 (93%) patients. Mutations in KIT (D816V, n=19; D816H/Y, n=5; F522C, n=1) were detected in 25 of 28 (89%) patients and prognostically relevant additional mutations in SRSF2, ASXL1 or RUNX1 (S/A/Rpos) in 13 of 25 (52%) patients. Overall response rate in 18 treatment-naïve patients was 5 of 12 (42%) on midostaurin and 1 of 6 (17%) on cladribine, and after switch 1 of 4 (25%) on midostaurin and 0 of 3 on cladribine, respectively. S/A/Rpos adversely affected response to treatment and progression to secondary mast cell leukemia (n=6) or acute myeloid leukemia (n=3) while on treatment (P<0.05). The median overall survival from mast cell leukemia diagnosis was 17 months as compared to 44 months in a control group of 124 patients with advanced systemic mastocytosis but without mast cell leukemia (P=0.03). In multivariate analyses, S/A/Rpos remained the only independent poor prognostic variable predicting overall survival (P=0.007). In conclusion, the molecular signature should be determined in all patients with mast cell leukemia because of its significant clinical and prognostic relevance.